RELIGIOUS FANATICISM AND ITS CHALLENGES TO CHARACTER EDUCATION IN CONTEMPORARY MUSLIM SOCIETIES - Arifin Marpaung; Ardiansyah Putra Ritonga; Dasril Adiafari; Hafizah Syafitri; Rahma Yahya; Jamaluddin (Yayasan Amanah Nur Aman, 2026)
Religious fanaticism has emerged as a prominent social phenomenon in contemporary Muslim societies and poses significant challenges to the development of inclusive and moderate character education. Fanaticism is not merely an expression of strong religious commitment, but rather manifests as an exclusive and absolutist attitude that undermines core character values such as tolerance, empathy, and openness to social diversity. This study aims to analyze religious fanaticism as a multidimensional phenomenon and to examine its implications for character education within the context of contemporary Muslim societies. Employing a qualitative approach, this research adopts a library research method with a descriptive-analytical framework. Data were collected from scholarly books and peer-reviewed journal articles addressing religious fanaticism, religious moderation, and character education. The findings indicate that religious fanaticism functions as a structural challenge to character education by influencing religious culture, social relations, and educational practices. Therefore, character education developed through a contextual and moderation-based approach plays a strategic role in fostering reflective, inclusive, and socially harmonious religious attitudes. Such an approach positions character education not only as moral instruction but also as a long-term preventive strategy for addressing the social consequences of religious fanaticism.